Prostitution in Lithuania in 1935–1940 - Žuravliovaitė, Gintarė (Vilnius University Open Series, 2024)
The article analyses the peculiarities of prostitution regulation in Lithuania until the mid-1930s, with a focus on the significance of reforms carried out in 1935. The research revealed that while control over prostitution persisted, efforts were made to reduce factors of exploitation by imposing criminal liability primarily on those profiting the most from prostitution, such as brothel keepers and procurers. Furthermore, using criminal laws and archival material, the study examined the practices of law enforcement institutions - the police and the courts - in prostitution cases, as well as the conditions of brothel keeping and procuring, and the working and living conditions of prostitutes, along with their daily life aspects.
Keywords: prostitution; brothels; procurers; First Republic of Lithuania; abolitionism